2018
DOI: 10.1007/s11136-018-1823-6
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between retrospectively and contemporaneously collected patient-reported outcome measures (PROMs) in hip and knee replacement patients

Abstract: PurposeTo investigate the relationship between retrospectively and contemporaneously collected patient-reported outcome measures (PROMs) and the influence on this relationship of patients’ age and socio-economic status and the length of time.MethodsPatients undergoing hip or knee replacement in four hospitals who had completed a pre-operative questionnaire were invited to recall their pre-operative health status shortly after surgery. The questionnaires included a disease-specific (Oxford Hip Score; Oxford Kne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 27 publications
2
23
0
Order By: Relevance
“…There are three possible explanations. First, it may be that patients recall their prior QoL as worse than it was, although no such bias was detected in studies of elective surgery when retrospective and contemporary reports were compared 14 15. Second, it may be that patients’ baseline disease-specific QoL was already lowered due to the presence of subacute symptoms prior to their AMI, but were not at the clinical threshold that warranted medical attention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are three possible explanations. First, it may be that patients recall their prior QoL as worse than it was, although no such bias was detected in studies of elective surgery when retrospective and contemporary reports were compared 14 15. Second, it may be that patients’ baseline disease-specific QoL was already lowered due to the presence of subacute symptoms prior to their AMI, but were not at the clinical threshold that warranted medical attention.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the feasibility of employing PROMs in emergency NHS admissions, an exploratory feasibility study was conducted in patients admitted with ST-segment-elevation myocardial infarction (STEMI) 13. Success of recruiting patients soon after admission and of obtaining their recollected state of health prior to their admission to provide a baseline assessment has been reported 13–15…”
Section: Introductionmentioning
confidence: 99%
“…20 Patient Cohorts: Hip Arthroplasty, Emergency Laparotomy and PCI EQ-5D from patients (n= 244) who had undergone hip arthroplasty (primary operation or revision surgery) in one of four NHS hospitals reported their pre-operative health status retrospectively in the immediate post-operative period prior to their discharge from hospital (Health Research Authority ethics approval was obtained from North East -Newcastle & North Tyneside 2 Research Ethics Committee (REC Ref: 16/NE/ 0081)). 4 The mean EQ-5D score of the cohort was similar to that for all patients' in a national audit in England. Information on comorbidity had previously been collected in a preoperative questionnaire and covered: heart disease (for example, angina, heart attack or heart failure), high blood pressure, problems caused by a stroke, leg pain due to poor circulation, lung disease, diabetes, kidney disease, liver disease, cancer (within in the last 5 years), diseases of the nervous system (for example, Parkinson's disease or multiple sclerosis), depression.…”
Section: Eq-5dmentioning
confidence: 53%
“…That study found strong agreement between retrospective and contemporary disease-specific PROs and EQ-5D, with intra-class correlation coefficients of 0.8 for the disease-specific PROs (Oxford Hip Score and Oxford Knee Score), and 0.6 for the EQ-5D. 3,4 An alternative approach that has been suggested is to derive expected PRO scores from respondents to general population surveys. Nine of the ten studies that have compared retrospective and population PRO scores have been conducted with trauma patients.…”
Section: Introductionmentioning
confidence: 93%
“…The reliability of patients’ recalling their prior health status via the use of a retrospective PROM has been demonstrated in six studies mostly in the USA. 19 20 To determine the feasibility of employing PROMs in emergency admissions, we undertook two exploratory studies, one on a medical condition and the other in surgery (emergency laparotomy). Patients’ recollected state of health prior to their admission was collected shortly after their laparotomy but before discharge from hospital to provide a baseline assessment.…”
Section: Introductionmentioning
confidence: 99%